Concepts and methods for strategy building and tactical adherence: a case study in football - Cordes, O.; Lamb, P. F.; Lames, M. (International Journal of Sports Science and Coaching, 2012)
This investigation looked at the on-field strategic planning of a professional German soccer club, how the strategic plans were adhered to in competition and how they were adjusted following matches. The methods presented in this article combine qualitative and quantitative techniques and are central to being able to assess objectively strategic plans and playing tactics. The coaching philosophy is a main contributor to the strategic plans, aspects of the match which were directly related to the coaching philosophy were less susceptible to change throughout the season. Additionally, adherence to strategic plans increased as the season progressed and was higher for home matches compared to away. The methods presented in this article have led to a new model of strategic planning, assessment of the quality of strategic plans put in place and the team's adherence to those strategies so that plans for upcoming matches can be optimised. The methods presented and the model for strategic planning and assessment can be used for other sports.